The implementation of online learning during the COVID-19 pandemic regarding students' mathematics learning outcomes - Rahmatia Rahmatia; Azis Azis (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
This study aimed to determine how well online learning was used during the Covid-19 pandemic regarding the academic outcomes for class VII students at SMP Negeri 38 Buton. This study was an experiment in research methodology. The population of this study was made up of all of the class VII students from SMP Negeri 38 Buton, which had two classes. Twenty students of class VII1 served as the experimental class, and twenty students of class VII2 served as the control class, and samples were collected using random sampling. In this study, tests were used as data-gathering methods. Descriptive and inferential statistics were employed in the data analysis for this investigation. According to the research findings, class VII students at SMP Negeri 38 Buton did not benefit from online learning during the Covid-19 pandemic regarding their learning outcomes.